Intestinal Parasitosis in Severely Malnourished Children at a Hospital in the City of Maracaibo, Venezuela - Adriana Maldonado; Angela Bracho; Zulbey Rivero Rodríguez; Teresa Atencio; Nelly de Molano; Ellen Acurero; Marinella Calchi; Rafael Villalobos (Kasmera, 2012)
To compare the prevalence of intestinal parasites in children with severe malnutrition in the Nutritional Recovery Unit at the Chiquinquirá Hospital of Maracaibo, State of Zulia, with eutrophic children attending consult for healthy children at the same hospital, stool examinations were performed for 50 seriously malnourished children and 50 eutrophic children by direct examination, using the concentration technique (Ritchie) and Ziehl Neelsen. Among the protozoa, Cryptosporidium sp. ranked first, with 14% in the group of severely malnourished and Giardia lamblia in 20% of the eutrophic children. Of the identified helminths, Trichuris trichiura prevailed, with 12% in the malnourished group, while Ascaris lumbricoides took first place with 8% in the eutrophic group. No statistically significant difference was found between the prevalence of parasites in general with age, sex or malnutrition, or between polyparasitism versus monoparasitism. The extent to which malnutrition and intestinal parasites relate is difficult to clarify, since malnutrition is a multifactorial condition that depends on the parasite species present, intensity of the parasitosis, immunologic and genetic characteristics of the host, the socio economic environment in which the individual develops and other factors.